Dinamika Interaksi dalam Kelompok Praktikum Anatomi Hewan - Mazwar Ismiyanto; Harsono Harsono; Sutama Sutama; Anam Sutopo; Budi Murtiyasa; Hernawan Sulistyanto (Mathematics Education Study Program, 2025)
The purpose of this study was to gain a better understanding of how students interact with each other in the Animal Anatomy practicum group. This study used qualitative research methods with a case study approach. Observations, interviews, and participatory document analysis were used to collect data. The results showed that many patterns of interaction occur in the Animal Anatomy practicum. These include the learning methods used, how many people are involved in group discussions, and the power dynamics among group members. This research has implications for designing lessons that encourage students to work together and participate in Animal Anatomy classes. The implication is that it is necessary to design lessons that take into account the diversity of learning styles and interaction preferences of students, as well as raising awareness of power dynamics in the context of group learning. Further research could explore how these factors influence learning achievement and the quality of students' experience in the Animal Anatomy practicum.